Analiza kierunków rozwoju usług na terenach wiejskich województwa zachodniopomorskiego w latach 2000–2006 - Kondratowicz-Pozorska, Jolanta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The paper presents analysis of directions of services development in rural areas in areas of West Pomeranian region in years 2000–2006. In this region there was research, by which author wanted to compare status of services from 2000 with status of services at the end of 2006. Analysis consists mostly of comparison of amount of employees in particular services (general in West Pomeranian and in rural areas). Next step was to present notes to service receivers, meaning owners of farms that were using or still use the services delivered in their place of living. Research was done on random probe in amount of 2500 farmers. There was also used data from Main Statistical Office of Szczecin (Wojewódzki Urząd Statystyczny w Szczecinie). Development of services in rural areas in eyes of farmers is definitely different from level of service development in towns and cities